KONTRIBUSI RELIGIUSITAS DALAM RASIONALITAS KONSUMSI RUMAH TANGGA MUSLIM - Anton Bawono (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
The purpose of this study was to determine whether a Muslim in belonged toexcessive consume or are still proportional. This study uses the entire householdpopulation of Muslims who already live independently in the province of DaerahIstimewa Yogyakarta. While the sample used by 109 respondents. Methods of analysisby looking at the value of average propensity to consume (APC), if the value of theAPC 1, this illustrates that the Muslim isrof consumption or excessive, and otherwiseit is called a proportional or rational. The analysis showed that the consumptionbehavior of Muslims households a sample of this with the APC rate is less than 1,while the scoring level of religiosity respondents using a scale of 0-10 depicts theaverage respondent is in a position high enough level of religiosity. Based on thefindings in this study, it can be concluded that the level of consumption of aMuslim is still rational and not excessive. One cause of consumption rationality ofa Muslim is the level of religiosity, so that consumption is not excessive.